Equilibrium studies for the removal of manganese (Mn) from aqueous solution using natural zeolite from West Java, Indonesia - Ali Munawar; Djoko Mulyanto; RR Dina Asrifah (Journal of Degraded and Mining Lands Management, 2023)
Manganese (Mn) is one of the heavy metals found in industrial wastewater, such as acid mine drainage, which has caused serious environmental problems worldwide. This equilibrium study was carried out to determine the maximum capacity of natural zeolite towards manganese removal from made aqueous solution as affected by zeolite quantity, particle size, activation temperature, and initial pH of the solution. The natural zeolites obtained from Tasikmalaya, West Java, Indonesia, were crushed and filtered into three groups of diameters: <0.5, 1-2, and 2-4 mm. Each group was divided into two sub-groups, one sub-group was heated in a muffle furnace at 250 oC for two hours, and the other sub-group was left at room temperature (25 oC). This experiment consisted of two sections. Section one was physical and chemical characterizations of the natural zeolite, using Scanning Electron Microscopy (SEM), X-Ray Diffraction, and X-Ray Fluorescence techniques. The second section was equilibrium studies using two series of 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, and 5 g of natural zeolites of each sub-groups, then respectively added with 50 mL of a solution containing 50 ppm Mn having pH of 5.5 and 7.0. All suspensions were shaken for 24 h and filtered. The filtrates were red for total dissolved Mn using Atomic Adsorption Spectrophotometer (AAS). Freundlich and Langmuir isothermic models were fitted to the collected data to describe the adsorptive behaviour of Mn toward natural zeolites. Data showed that 0.5 g of natural zeolite had removed the remarkably highest Mn from the solution, regardless of the size of the particles, thermal treatment, and initial solution pH. The smallest size of zeolite particle and higher initial solution pH tended to increase the adsorptive capacity of the natural zeolite toward Mn. The Freundlich isothermic model fitted better to Mn adsorption behaviour than the Langmuir model.